2018
DOI: 10.1002/pssr.201800505
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Charge Collection Promoted by Interface Passivation Using Amino Acid Toward High Performance Perovskite Solar Cells

Abstract: Interfacial modification of organolead halide perovskites (OHPs) has shown to be a promising strategy to improve the quality of OHPs film. In this work, a bipolar amino acid molecule, L‐Leucine (LL), have been introduced to the anti‐solvent solution to induce the formation methylammonium lead triiodide (MAPbI3) perovskite films. The morphology, crystal structure, and optoelectronic property of perovskite films are systematically studied, where the bipolar LL plays a key role. By employing the LL‐modified perov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…The obtained PCE is the highest among the biomaterial‐enhanced PSCs reported thus far (Figure 5e; Table S5, Supporting Information). [ 23,61–73 ] Moreover, to the best of our knowledge, this is the first time that the PCE of a biomaterial‐enhanced PSC was certified.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The obtained PCE is the highest among the biomaterial‐enhanced PSCs reported thus far (Figure 5e; Table S5, Supporting Information). [ 23,61–73 ] Moreover, to the best of our knowledge, this is the first time that the PCE of a biomaterial‐enhanced PSC was certified.…”
Section: Resultsmentioning
confidence: 94%
“…e) Efficiency and year when the respective perovskite solar cells supplemented with bio‐material additives were reported. [ 23,62–74 ]…”
Section: Resultsmentioning
confidence: 99%
“…Wu and collaborators also employed commercial l-leucine to improve electron injection from CH 3 NH 3 PbI 3 to the TiO 2 layer. [359] The group reported that the bipolar nature of l-leucine improves the quality of the perovskite films, promotes the charge transfer at the interface, and protects the films from H 2 O/O 2 penetration. This is ascribed to the ability of l-leucine to form a passivation layer on the face of the perovskite film.…”
Section: Charge Transport Layermentioning
confidence: 99%
“…However, for MA 80 (B 4 PI) 20 PbI 3 showed a slight blue shi, which agrees with the emission spectrum. According to other studies, this displacement is associated with the presence of 2D-3D perovskite in the lm 47,48 which is conrmed by the XRD analysis. Even so, problems associated with the quality of the perovskite lm showed less intensity in PL (Fig.…”
Section: Thin Lm Stability Testsmentioning
confidence: 56%